Analisis Program Layanan Zakat Digital terhadap Penerimaan Zakat dengan Pendekatan Data Envelopment Analysist (DEA) pada Badan Amil Zakat Nasional - Bunga Larasati Pujianto; Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research aims to determine the level of efficiency of the digital zakat program on the acceptance of BAZNAS Zakat with a method Data Envelopment Analysist (DEA) Approach. The sample of this research are operational costs and zakat receipts for digital zakat of the National Amil Zakat (BAZNAS). This research used an analytical tool of DEA (Data Envelopment Analysis) with variable Constant Return to Scale (CRS) production approach and output oriented. Variable inputs are Zakat funds (I1), Operational Costs (I2), and Digital Zakat Funds (O1). The results of this research on 2016-2018 that digital zakat service program shows the optimal level of efficiency by testing using the Data Envelopment Analysist method with the Constant Return to Scale (CRS) model.